Drug Industry in Kashmir - Mehta, M. L. (Indian Forester, 1948)
DiscusseS the problems connected with the natural and artificial regeneration of Champion's A-3. Dry Peninsular Sal. Natural regeneration, though scanty, is probably adequate both in Bihar, Orissa and the Central Provinces. The principal adverse factor is drought. Establishment period would seem to be vcry long and it is important to have adnlllcc growth on the ground at the time of regeneration operations. Shade is essential for successful regeneration and a mixture of Imv and high shade seems to be beneficia1. Shrubs and undcrgrmvth rarely cause serious difficulty, neither do climbers, but grass may be detrimental. Flemingia chappar has beon suggested to be a good nurse. Burning is unquestionably detrimental in every phase of regeneration. Grazing is also probably an adverse factor, but much is not known about the effect and manipulation of soil. Coppice regeneration is generally good. Artificial regeneration is of subsidiary importance. There do not seem to be any large plantations, neither is there any record of taungra plantations, which have however been recommended for Bihar and Orissa. Direct Rowing is the only method of propagation. Weedings, early tending and soil working are important. Tephrosia candida may be a good nurse crop. Very little inforrnation is available about costs. Keeping a mixture of species at the time of thinnings would seem to be favourable to regeneration.